(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of the position of Great Britain during the Eastern crisis of 1875- 1878 years, whether it had features of so called policy of “splendid isolation” which was held by this country in the 2nd part of the XIXth century.